2015
DOI: 10.1039/c4ra13261k
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide biosurfactant from Bacillus clausii BS02 using sunflower oil soapstock: evaluation of high throughput screening methods, production, purification, characterization and its insecticidal activity

Abstract: A total of 76 bacterial isolates were screened for biosurfactant activity using 16 different high throughput screening methods. Based on phenotypic characteristics, 16S rDNA sequencing and FAME profiling, isolate BS02, identified as Bacillus clausii BS02 produced a biosurfactant (2.6 g l -1 ) when grown in basal salts mineral medium with sunflower oil soapstock (3% w/v) at 30 o C and 120 rpm after 42 h. The cell free broth showed 82% emulsification activity, critical micelle concentration of 45 mg l -1 and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 44 publications
(83 reference statements)
2
14
0
1
Order By: Relevance
“…55,56 The vegetable oils, such as sunower, peanut, corn, coconut, palm, soybean and olive oil, have been extensively utilized for biosurfactant production. [57][58][59] Reports indicated that the yield of biosurfactant was greatly affected by fermentation substrates. 60 Not only the substrates, but also the fermentation conditions will improve the production.…”
Section: Biosurfactant Production Kinetics Of Pseudomonas Sp Cq2mentioning
confidence: 99%
“…55,56 The vegetable oils, such as sunower, peanut, corn, coconut, palm, soybean and olive oil, have been extensively utilized for biosurfactant production. [57][58][59] Reports indicated that the yield of biosurfactant was greatly affected by fermentation substrates. 60 Not only the substrates, but also the fermentation conditions will improve the production.…”
Section: Biosurfactant Production Kinetics Of Pseudomonas Sp Cq2mentioning
confidence: 99%
“…For the first time in 2015, cyclic lipopeptides produced by B. clausii DTM1, exhibited herbicidal activity in addition to insecticidal activity against aphid species Plutella xylostella and Diabrotica balteata [34]. Further, the strain BS02 was active against pulse beetle and mealybug [35]. We isolated a strain of B. clausii from the larvae breeding site and, when tested on the mosquito larvae, its supernatant fraction exhibited a high insecticidal activity with 75% of larva mortality.…”
Section: Discussionmentioning
confidence: 99%
“…4). In view of the results, it is anticipated that the biosurfactant obtained could be used for solubilizing high fat and oil prevalent in dairy industry wastewater and in cosmetic industries [22,23].…”
Section: Emulsification Activitymentioning
confidence: 99%